Assembling Interrelations Between Low Socioeconomic Status and Acute Alcohol-Related Harms Among Young Adult Drinkers. (June 2015) - Hart, Aaron
It is well established that alcohol-related harm is disproportionately prevalent among low socioeconomic status (SES) drinkers despite their lower consumption of alcohol, but epidemiological investigations have been unable to explain those links causally. I argue that this inability arises from the consumption-as-harm proposition, which proceeds from the assumption that alcohol acts in stable and predictable ways. In this model, "social factors" have been associated with increasing or decreasing harms by modulating consumption, but their other transformations of alcohol effects have not been registered. Stepping away from this model, I deploy the notion of the causal assemblage, which was developed in science and technology studies and has recently been applied in studies of alcohol and other drug (AOD) use. I analyze data from interviews with a convenience sample of low SES young adult drinkers and develop case studies of drinking events. I demonstrate that, in the case studies, alcohol-related harms are co-produced by troubled family and ethnic patterns of relations to alcohol and associated memories, enforcement of gender norms in public spaces, and a lack of access to private drinking settings. These insights are significant because they make visible the social forces co-producing alcohol-related harms and demonstrate the limitations of a model of causality commonly deployed in AOD studies.